Characteristics of Students in Traditional Versus Alternative High Schools: A Cross-Sectional Analysis of Enrollment in One Urban District. (September 2017) - Perzigian, Aaron B.; Afacan, Kemal; Justin, Whitney; Wilkerson, Kimber L.
Urban school districts are comprised of many diverse high school environments including comprehensive neighborhood schools as well as a variety of smaller alternative models that focus on innovative practices, behavior remediation, or academic recovery. In terms of enrollment distribution, urban school districts are increasingly offering nontraditional school placement options for students presenting academic and behavioral difficulty or for students seeking specific curricular emphasis or pedagogy, including—but not limited to—use of school choice voucher programs. In this study, we examined student distribution across school types in one large urban district to investigate enrollment patterns with regard to gender, race, socioeconomic status, and disability status. The results of this cross-sectional analysis indicated significant disproportionality in student demographics within different school types, including overrepresentation of African American students, male students, and students with disabilities in restrictive and segregated alternative schools; overrepresentation of White students and female students in self-selected and innovative alternative schools; and underrepresentation of Hispanic and Asian students in remedial alternative schools. Implications of this disproportionality for policy and practice are discussed.